Access to airports : A case study for the San Francisco Bay Area - Eric Pels; Peter Nijkamp; Piet Rietveld (European Regional Science Association (ERSA), 1998)
In a liberalized aviation market airports in a multiple airport region will have to compete with substitute airports for origin / destination passengers (and also transfer passengers). Passengers have to take a number of decisions; the have to choose airports, airlines and airport access modes (given that they already have decided they will fly). These choices can be made simultaneously or sequentially. These choices depend on a number of variables such as airport taxes and airport access times, frequency of service offered by the airline and airfare, and availability and cost of the access mode. Moreover, these choices may depend upon depend upon each other; depending on whether these choices are taken sequentially or simultaneously. The choice of airport access mode has been studied only sparsely in the literature; notable exceptions are Bondzio (1996) and Harvey (1986). Both authors use multinomial logit models with access time and cost as the explanatory variables. Moreover, Bondzio (1996) also estimates nested logit models and finds that business travelers make the choices of airport and access mode sequentially while leisure travelers make the choice simultaneously. In this paper we will analyze the choice of access mode in the San Francisco Bay Area in relation to the choice of airport by means of a nested logit model. The results will then be compared to the results (for Germany) of Bondzio (1996) to see if there are regional (international) differences in the determinants of access mode choice and Harvey (1986), who analyzed the same problem using data for 1990, to see whether the determinants have changed over time. Keywords : airport choice, access modes, (nested) logit models.
Keywords: 330